COVID-19 Pandemic—Knowledge, Attitudes, Behaviours, and Actions among Faculty of Health Sciences Students - Anna Stefanowicz-Bielska (MDPI AG, 2021)
The aim of the study was to assess the level of knowledge about COVID-19 disease and preventive behaviour of undergraduate students of nursing, midwifery, and emergency medicine. Material and Methods: An electronic survey was conducted among students of nursing, midwifery, and emergency medicine during the COVID-19 pandemic, from 8 April 2021 to 6 June 2021 in the Pomeranian Voivodeship. Results: A total of 37 men and 238 women participated in the study. A moderate level of knowledge was found in 88% and high in 11% of students Midwifery students had a higher level than nursing students (p = 0.002) and students of emergency medicine (p = 0.003). The female gender is much more afraid of SARS-CoV-2 virus infection (p = 0.021). The most common preventive measure was to avoid people who coughed or had a cold (93%). Only 84% of students were vaccinated. Students who had a high level of knowledge more often avoided people who coughed or had a cold (p = 0.03) and gave up on meeting with friends (p = 0.02). Conclusions: Constant education of students on the principles of dealing with the risk of infection with SARS-CoV-2 is necessary. It is important to continually motivate students to adhere to the principles of prevention. In the face of the existing epidemiological threat, there is a need to change the curricula for the fields of health sciences by adding the subject infectious diseases—clinic and nursing, with special attention to practical aspects.